Case Report: A Rare Truncating Variant of the CFHR5 Gene in IgA Nephropathy - Guzzo, Gabriella; Sadallah, Salima; Fodstad, Heidi; Venetz, Jean-Pierre; Rotman, Samuel; Teta, Daniel; Gauthier, Thierry; Pantaleo, Giuseppe; Superti-Furga, Andrea; Pascual, Manuel (Frontiers in Genetics, 2021)
IgA nephropathy (IgAN) is the most common primary glomerulonephritis worldwide. Despite appropriate therapy, 20-40% of affected-patients evolve towards end-stage kidney disease (ESKD). Mesangial IgA deposits are the hallmark of IgAN, and complement deposition (C3) seems to differentiate latent IgA mesangial deposits from active IgAN. Atypical haemolytic uremic syndrome (aHUS), another disease in which complement plays an important role, is caused by inherited or acquired deregulation of the alternative pathway (AP) of complement. A subgroup of IgAN shows thrombotic microangiopathy (TMA) lesions in kidney biopsies, the histological characteristic of aHUS. Genetic variants of complement Factor H (CFH), known to be present in aHUS, have been associated with rapidly progressive forms of IgAN and a clinical pattern of aHUS. Genome-wide association studies (GWAS) have confirmed that the 1q32 region, encoding for CFH and its related proteins, is an IgAN susceptibility locus. A 30 year-old man was admitted for seizures and malignant hypertension. The kidney biopsy showed IgAN associated with features of TMA. Despite five plasma exchanges, the patient remained dialysis-dependent, and ESKD was diagnosed. Functional and genetic complement analysis were performed. A monoallelic protein-truncating, likely loss-of-function variant was identified in the CFHR5 gene. Eculizumab is the treatment of aHUS. As it has been successfully used in a few cases of rapidly progressive IgAN, it was decided to administer eculizumab over a period of twelve months in addition to the usual immunosuppression for renal transplantation. After a follow-up of three years, there was no clinical disease recurrence. Systematic biologic and genetic screening of complement in individuals with IgAN might be useful to better delineate the role of the AP of complement in renal disease progression, and this may have therapeutic implications.